PENGEMBANGAN MEDIA PEMBELAJARAN MATEMATIKA BERBASISIS ADOBE FLASH UNTUK PESERTA DIDIK KELAS VIII - Maghfiroh, Ida; Khotimah, Khusnul; Verdianingsih, Eliza (Exact Papers in Compilation (EPiC), 2019)
ABSTRACT The research was used R&D (Research and Development) research method that aims to produced and describe mathematic learning media based on Adobe Flash CS3. Researcher is adapted from R&D (Research and Development) research method by ADDIE. The first experts material give “4.5” score to the researcher it was “Valid” category. The second experts material give “4.7” score to the researcher it was “Valid” category, and researcher get “4.2” score from expert media it was “Valid” category. The result of questionnaires for students responses about mathematic learning media based on Adobe Flash CS3 get a percentage score “89.5%” it was “Very Good” category. Then, the result of pre test students was obtained average score “33.7” it means that all of students have low score below “KKM” which is ≤ 75. While, the result of post test students was obtained average score “82” it means that all of students get the high score on the top of “KKM” which is ≥ 75. Then, the final score of attitude assessment is “2.4” it was “Good” category. It means that students have a good attitude. The final score of performance assessment is “2.5” it was “Good” category. It means that students have a good performance. Based on the result above, the researcher conclude that mathematic learning media based on Adobe Flash CS3 relations and functions, feasible and valid to used in learning mathematic. Keyword : Mathematic Learning Media Based on Adobe Flash CS3